Polymer Composites, Biocomposites. - Thomas, Sabu (Wiley, 2013)
Polymer composites are materials in which the matrix polymer is reinforced with organic/inorganic fillers of a definite size and shape, leading to enhanced performance of the resultant composite. These materials find a wide number of applications in such diverse fields as geotextiles, building, electronics, medical, packaging, and automobiles. This first systematic reference on the topic emphasizes the characteristics and dimension of this reinforcement. The authors are leading researchers in the field from academia, government, industry, as well as private research institutions.